207-257 GHz Integrated Sensing Readout System with Transducer in a 130-nm SiGe BiCMOS Technology - Wang, D.; J Yun; MH Eissa; M Kucharski; K Schmalz; A Malignaggi; Y. Wang; J Borngräber; Y Liang; HJ Ng; QH Le; DK Huynh; et al. (2019 IEEE MTT-S International Microwave Symposium (IMS), 2019)
This paper presents a wideband integrated dielectric sensor with read-out circuit at 207-257 GHz in SiGe BiCMOS technology. The sensing element is equipped by a resonator that provides a bandpass frequency response which is varied in accordance to the carried permittivity change of the device under test. This variation can be sensed and recorded as the change of output voltage of an integrated 207-257 GHz 2 port vector network analyzer readout circuit. The demonstration of aforementioned readout system is verified by measuring the output of mixers as the reference, reflected and measured channel, and the uncalibrated S parameters of readout with different samples.